Study of dynamic re-crystallization and copper precipitation of low carbon steel in single hit and double hit plain strain compression. (2017) - Kumar, Pawan; Banerjee, M.K.; Hodgson, Peter; Choudhray, Amit Roy
Abstract: The primary aim of the present investigation is to study the effect of temperature and strain rate on dynamic re-crystallization behaviour in 0.05C-1.52Cu-1.51Mn steel. The flow diagram for single hit compression as well as double hit compression with a pre-strain of 0.4 using thermo-mechanical simulator (Gleeble) in plain strain compression is obtained. It is found that single hit compression shows dynamic re-crystallization behaviour while double hit compression shows dynamic recovery. There is an indication of serrations in flow diagram at lower deformation temperature and strain rate is observed in case of double hit compression. The Cu precipitate of size 10 nm is found in the process adopted in the experimentation. It is also observed that high deformation temperature